Comparison of diagnostic performances of HDV-RNA quantification assays used in clinical practice: Results from a national quality control multicenter study - Salpini, Romina; Piermatteo, Lorenzo; Caviglia, Gian Paolo; Bertoli, Ada; Brunetto, Maurizia Rossana; Bruzzone, Bianca; Callegaro, Annapaola; Caudai, Cinzia; Cavallone, Daniela; Chessa, Luchino; Coghe, Fernando; Coppola, Nicola; et al. (Journal of clinical virology, 2025)
A reliable quantification of hepatitis D virus (HDV) RNA is of paramount importance for monitoring patients under antiviral therapy. This quality control study compares the diagnostic performances of quantitative HDV-RNA assays used in clinical practice. Two HDV-RNA sample panels were quantified in 30 centers by RoboGene (N = 9 laboratories), EurobioPlex (N = 7), RealStar (N = 4), AltoStar (N = 1), Bosphore (N = 3), Bosphore-on-InGenius (N = 1), Dia.Pro (N = 2), Nuclear-Laser-Medicine (N = 1) and 3 in-house assays. Panel A and B comprised 8 serial dilutions of WHO/HDV standard (range: 0.5–5.0 log10 IU/ml) and 20 clinical samples (range: 0.5–6.0 log10 IU/ml), respectively. The following parameters were determined: sensitivity by 95 % LOD (limit of detection), precision by intra- and inter-run CV (coefficient of variation), accuracy by the differences between expected-observed HDV-RNA, linearity by linear regression analysis. 95 % LOD varied across assays and centers underlining heterogeneous sensitivities: AltoStar had the lowest 95 % LOD (3 IU/ml) followed by RealStar (10 [min–max: 3–316] IU/ml), Bosphore-on-InGenius (10 IU/ml), RoboGene (31 [3–316] IU/ml), Nuclear-Laser-Medicine (31 IU/ml) and EuroBioplex (100 [100–316] IU/ml). Moreover, 6 assays (RoboGene, EurobioPlex, RealStar, AltoStar, Nuclear-Laser-Medicine and In-house) showed <0.5 log10 IU/ml differences between expected and observed HDV-RNA for all dilutions while other assays had >1 log10 IU/ml underestimations. RealStar, Bosphore-on-InGenius and EurobioPlex had the highest precision (mean intra-run CV < 20 %). Inter-run CV was higher for all assays, with CVs < 25 % for RealStar, AltoStar, Nuclear-Laser-Medicine and EurobioPlex. Seven assays (RoboGene/AltoStar/RealStar/EurobioPlex/Nuclear-Laser-Medicine/In-house) showed a good linearity (R2 > 0.90), but for HDV-RNA < 1000 IU/ml only Bosphore-on-InGenius, AltoStar, RealStar and Robogene showed a R2 > 0.85. This study underlines heterogeneous sensitivities (inter- and intraassays), that could hamper proper HDV-RNA quantification, particularly at low viral loads. This raises the need to improve the diagnostic performance of most assays for properly identifying virological response to anti-HDV drugs. ●The assays for HDV-RNA quantification need to optimize the performances at low HDV-RNA concentrations.●The laboratories should mitigate inter-laboratory and inter-assay variability by standardizing procedures and by favouring automation.●The use of sensitive assays is important for the proper monitoring of virological response to anti-HDV drugs and for optimizing therapeutical approaches aimed at setting-up a finite course of anti-HDV treatment.